The phonology of Italian - Krämer, Martin, 1969- (Phonology of the world's languages., 2009)
This book provides an overview of the phonology of Italian. It covers the different levels of analysis from individual sounds up to the phrasal level. It focuses on the most widely dispersed features of the language reflecting its significant regional and social variation and its most prominent regionally restricted patterns. - ;This book provides an overview of the phonology of Italian. It covers the different levels of analysis from individual sounds up to the phrasal level. It focuses on the most widely dispersed features of the language reflecting its significant regional and social variat.